Complex adjustments of photosynthetic potentials and internal diffusion conductance to current and previous light availabilities and leaf age in Mediterranean evergreen species Quercus ilex - NIINEMETS, Ü L. O.; CESCATTI, ALESSANDRO; RODEGHIERO, MIRCO; TOSENS, TIINA (Plant, Cell & Environment, 2006)
Mature non-senescent leaves of evergreen species become gradually shaded as new foliage develops and canopy expands, but the interactive effects of integrated light during leaf formation (QintG), current light (QintC) and leaf age on foliage photosynthetic competence are poorly understood. In Quercus ilex L., we measured the responses of leaf structural and physiological variables to QintC and QintG for four leaf age classes. Leaf aging resulted in increases in leaf dry mass per unit area (MA), and leaf dry to fresh mass ratio (DF) and decreases in N content per dry mass (NM). N content per area (NA) was independent of age, indicating that decreases in NM reflected dilution of leaf N because of accumulation of dry mass (NA = NM MA). MA, DF and NA scaled positively with irradiance, whereas these age-specific correlations were stronger with leaf growth light than with current leaf light. Area-based maximum ribulose 1,5-bisphosphate carboxylase/oxygenase (Rubisco) carboxylase activity (VcmaxA), capacity for photosynthetic electron transport (JmaxA) and the rate of non-photorespiratory respiration in light (RdA) were also positively associated with irradiance. Differently from leaf structural characteristics, for all data pooled, these relationships were stronger with current light with little differences among leaves of different age. Acclimation to current leaf light environment was achieved by light-dependent partitioning of N in rate-limiting proteins. Mass-based physiological activities decreased with increasing leaf age, reflecting dilution of leaf N and a larger fraction of non-photosynthetic N in older leaves. This resulted in age-dependent modification of leaf photosynthetic potentials versus N relationships. Internal diffusion conductance (gm) per unit area (gmA) increased curvilinearly with increasing irradiance for two youngest leaf age classes and was independent of light for older leaves. In contrast, gm per dry mass (gmM) was negatively associated with light in current-year leaves. Greater photosynthetic potentials and moderate changes in diffusion conductance resulted in greater internal diffusion limitations of photosynthesis in higher light. Both area- and mass-based gm decreased with increasing leaf age. The decrease in diffusion conductance was larger than changes in photosynthetic potentials, leading to larger CO2 drawdown from leaf internal air space to chloroplasts (ΔC) in older leaves. The increases in diffusion limitations in older leaves and at higher light scaled with age- and light-dependent increases in MA and DF. Overall, our study demonstrates a large potential of foliage photosynthetic acclimation to changes in leaf light environment, but also highlights enhanced structural diffusion limitations in older leaves that result from leaf structural acclimation to previous rather than to current light environment and accumulation of structural compounds with leaf age.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: CO2 drawdown; growth irradiance; leaf age; leaf structure; mesophyll conductance; nitrogen content; photosynthetic capacity

Complex adjustments of photosynthetic potentials and internal diffusion conductance to current and previous light availabilities and leaf age in Mediterranean evergreen species Quercus ilex - NIINEMETS, Ü L O; CESCATTI, ALESSANDRO; RODEGHIERO, MIRCO; TOSENS, TIINA (Plant, Cell & Environment, 2006)
Mature non-senescent leaves of evergreen species become gradually shaded as new foliage develops and canopy expands, but the interactive effects of integrated light during leaf formation (QintG), current light (QintC) and leaf age on foliage photosynthetic competence are poorly understood. In Quercus ilex L., we measured the responses of leaf structural and physiological variables to QintC and QintG for four leaf age classes. Leaf aging resulted in increases in leaf dry mass per unit area (MA), and leaf dry to fresh mass ratio (DF) and decreases in N content per dry mass (NM). N content per area (NA) was independent of age, indicating that decreases in NM reflected dilution of leaf N because of accumulation of dry mass (NA = NM MA). MA, DF and NA scaled positively with irradiance, whereas these age-specific correlations were stronger with leaf growth light than with current leaf light. Area-based maximum ribulose 1,5-bisphosphate carboxylase/oxygenase (Rubisco) carboxylase activity (VcmaxA), capacity for photosynthetic electron transport (JmaxA) and the rate of non-photorespiratory respiration in light (RdA) were also positively associated with irradiance. Differently from leaf structural characteristics, for all data pooled, these relationships were stronger with current light with little differences among leaves of different age. Acclimation to current leaf light environment was achieved by light-dependent partitioning of N in rate-limiting proteins. Mass-based physiological activities decreased with increasing leaf age, reflecting dilution of leaf N and a larger fraction of non-photosynthetic N in older leaves. This resulted in age-dependent modification of leaf photosynthetic potentials versus N relationships. Internal diffusion conductance (gm) per unit area (gmA) increased curvilinearly with increasing irradiance for two youngest leaf age classes and was independent of light for older leaves. In contrast, gm per dry mass (gmM) was negatively associated with light in current-year leaves. Greater photosynthetic potentials and moderate changes in diffusion conductance resulted in greater internal diffusion limitations of photosynthesis in higher light. Both area- and mass-based gm decreased with increasing leaf age. The decrease in diffusion conductance was larger than changes in photosynthetic potentials, leading to larger CO2 drawdown from leaf internal air space to chloroplasts (ΔC) in older leaves. The increases in diffusion limitations in older leaves and at higher light scaled with age- and light-dependent increases in MA and DF. Overall, our study demonstrates a large potential of foliage photosynthetic acclimation to changes in leaf light environment, but also highlights enhanced structural diffusion limitations in older leaves that result from leaf structural acclimation to previous rather than to current light environment and accumulation of structural compounds with leaf age.
Keywords: CO2 drawdown; growth irradiance; leaf age; leaf structure; mesophyll conductance; nitrogen content; photosynthetic capacity

Pan-European δ13C values of air and organic matter from forest ecosystems - Hemming, Deborah; Yakir, Dan; Ambus, Per; Aurela, Mika; Besson, Cathy; Black, Kevin; Buchmann, Nina; Burlett, Regis; CESCATTI, ALESSANDRO; Clement, Robert; Gross, Patrick; Granier, André; et al. (Global Change Biology, 2005)
We present carbon stable isotope, δ13C, results from air and organic matter samples collected during 98 individual field campaigns across a network of Carboeuroflux forest sites in 2001 (14 sites) and 2002 (16 sites). Using these data, we tested the hypothesis that δ13C values derived from large-scale atmospheric measurements and models, which are routinely used to partition carbon fluxes between land and ocean, and potentially between respiration and photosynthesis on land, are consistent with directly measured ecosystem-scale δ13C values. In this framework, we also tested the potential of δ13C in canopy air and plant organic matter to record regional-scale ecophysiological patterns. Our network estimates for the mean δ13C of ecosystem respired CO2 and the related ‘discrimination’ of ecosystem respiration, δer and Δer, respectively, were −25.6±1.9‰ and 17.8 ±2.0‰ in 2001 and −26.6±1.5‰ and 19.0±1.6‰ in 2002. The results were in close agreement with δ13C values derived from regional-scale atmospheric measurement programs for 2001, but less so in 2002, which had an unusual precipitation pattern. This suggests that regional-scale atmospheric sampling programs generally capture ecosystem δ13C signals over Europe, but may be limited in capturing some of the interannual variations. In 2001, but less so in 2002, there were discernable longitudinal and seasonal trends in δer. From west to east, across the network, there was a general enrichment in 13C (∼3‰ and ∼1‰ for the 2 years, respectively) consistent with increasing Gorczynski continentality index for warmer and drier conditions. In 2001 only, seasonal 13C enrichment between July and September, followed by depletion in November (from about −26.0‰ to −24.5‰ to −30.0‰), was also observed. In 2001, July and August δer values across the network were significantly related to average daytime vapor pressure deficit (VPD), relative humidity (RH), and, to a lesser degree, air temperature (Ta), but not significantly with monthly average precipitation (Pm). In contrast, in 2002 (a much wetter peak season), δer was significantly related with Ta, but not significantly with VPD and RH. The important role of plant physiological processes on δer in 2001 was emphasized by a relatively rapid turnover (between 1 and 6 days) of assimilated carbon inferred from time-lag analyses of δer vs. meteorological parameters. However, this was not evident in 2002. These analyses also noted corresponding diurnal cycles of δer and meteorological parameters in 2001, indicating a rapid transmission of daytime meteorology, via physiological responses, to the δer signal during this season. Organic matter δ13C results showed progressive 13C enrichment from leaves, through stems and roots to soil organic matter, which may be explained by 13C fractionation during respiration. This enrichment was species dependent and was prominent in angiosperms but not in gymnosperms. δ13C values of organic matter of any of the plant components did not well represent short-term δer values during the seasonal cycle, and could not be used to partition ecosystem respiration into autotrophic and heterotrophic components.
Keywords: carboeuroflux; CO2 fluxes; ecosystem carbon budget; ecosystem respiration; isotopic discrimination; Stable isotopes; δ13C